Analisis Pengaruh Penambahan Ca(Oh)₂ Terhadap Kontaminasi Ion Magnesium (Mg²⁺) Berdasarkan Nilai Rheology Lumpur Pemboran Berbasis Air - Yohanes Ongky Miang; Joko Wiyono; Fatma Fatma (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research was conducted to evaluate the impact of magnesium ion (Mg²⁺) contamination and to assess the effectiveness of calcium hydroxide (Ca(OH)₂) as a treatment agent on the rheological behavior of water-based drilling mud. The experiment utilized 350 mL of water-based mud (WBM), which was contaminated with MgCl₂·6H₂O at concentrations of 2 g, 4 g, and 6 g. Subsequently, Ca(OH)₂ was added at dosages of 1 g, 2 g, and 3 g. The evaluated parameters included plastic viscosity (PV), yield point (YP), gel strength, filtration loss, mud weight, and pH in accordance with API standards. The findings revealed that magnesium contamination altered the rheological characteristics of the drilling mud, as indicated by a reduction in PV, increases in YP and gel strength, higher filtration loss values, and a decrease in pH. These changes suggest that the presence of Mg²⁺ negatively affects mud stability. Following the addition of Ca(OH)₂, the pH increased and returned to alkaline conditions, while the adverse effects of magnesium contamination on mud rheology were partially mitigated. Although several rheological parameters remained higher than those of the base mud, the treatment demonstrated its ability to improve mud performance by stabilizing its chemical condition and reducing the influence of magnesium ions. The results indicate that Ca(OH)₂ can be applied as a treatment material to reduce the adverse effects of magnesium ion contamination in water-based drilling mud. However, an appropriate dosage is still required to achieve optimum drilling fluid performance.